Evaluation of Antenatal Maternal Serum Biomarkers in Pregnancies Over 41 Weeks - Kansu Çelik, Hatice; Engin Üstün, Yaprak; Timur, Hakan; Yaman, Selan; Yılmaz, Saynur; Yapar Eyı, Elif Gül; Mollamahmutoğlu, Leyla (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: To examine association between maternal antenatal serum biomarkers and post-term pregnancies. STUDY DESIGN: Singleton pregnant women (n=186) managed at the Zekai Tahir Burak Women’s Health, Education and Research Hospital in Turkey from July 2010 to December 2010 were analyzed retrospectively. Maternal serum levels of PAPP-A, free β-hCG, AFP, HCG and unconjugated E3 were noted routinely in antenatal screening programs. We compared these biomarkers in pregnancies between 37 and 41 gestational weeks (n=73) and ≥41 (n=113) gestational weeks. RESULTS: There was no statistically significant difference in maternal PAPP-A, free beta-hCG, AFP, total hCG and unconjugated E3 levels between the two groups. Although birth weights were higher in pregnant women ≥41 weeks, this difference was not considered significant (p=0.19). There were no SGA babies in the group of post-term pregnancies. CONCLUSION: There were no statistically significant differences in maternal serum markers for pregnant women having their period of ≥41 gestational week.